SET A STRUCTURE OF OBJECTS WITH A HELP OF GROUPING TO TEN STRATEGY TO UNDERSTAND THE IDEA OF UNITIZING - Saliza Safta Assiti; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Journal on Mathematics Education, 2013)
The intention of the present study is to know how the pupils can learn to make a group of ten to understand the idea of unitizing. The pupils were given a contextual problem “Counting the Beads in order to promote their understanding about the idea of unitizing. The process of designing the problem was based on the 5 tenets of Indonesian Realistic Mathematics Education (IRME). The methods of this study was a design research. The researcher designed the Hypothetical Learning Trajectory (HLT) before conducting the lesson in the classroom. The result of this study showed that the pupils learned to make a group of any number then moved to make a group of twenty before using the group of ten as a strategy in finding the amount of the beads. The pupils set a structure of objects with a help of grouping to ten strategy to understand the idea of unitizing.